DEVELOPMENT OF ETHNOMATHEMATICS-BASED WORKSHEET ON TRANSFORMATION GEOMETRY - Ratu Sarah Fauziah Iskandar; Dewi Ranti; Nanang Priatna (Prima: Jurnal Pendidikan Matematika, 2022)
This study aims to analyze the effectiveness of ethnomathematics-based student worksheets with West Java batik motifs in solving students' mathematical problems. The research method used in this study is a quantitative method with the type of research only posttest control design. The population in this study were all students of class XI SMK Negeri 5 Bekasi. The sampling technique used in this study is a cluster random sampling technique. From the sampling results, it was found that 2 classes were used as the experimental class and the control class. The experimental class is a class whose learning uses ethnomathematics-based mathematics teaching materials, while the control class is a class whose learning does not use ethnomathematics-based mathematics teaching materials. Data collection techniques used are documentation method, observation method and test method. Data analysis technique used in this research is quantitative data analysis technique using t-test. Based on the results of the research and discussion that have been described, the conclusions that can be drawn are from the results of the calculation of the t-test of posttest data for the two classes, namely the control class and the experimental class, it is obtained that the 2-way (t-tailed) significance value is 0.000 < 0.05 . So there is a significant difference between the control group and the experimental group.